Impact of corporate governance on performance, risk and disclosure - Htay, Sheila Nu Nu (Lambert Academic Publishing, 2012)
The issue of corporate governance is not new since it emerged with the birth of the corporations. However, it becomes an important issue to the Asians, especially Malaysians, due the 1997/98 economics crisis. This study examines the impact of corporate governance on performance, risk and disclosure of the Malaysian listed banks over the period of 1996 to 2005. From the generalized least squares panel data regression; the results show that corporate governance mechanisms such as board leadership structure, board composition and board size as well as ownership variables such as director ownership, institutional ownership and block ownership do not play their roles significantly and consistently in three aspects. i.e. performance, risk and disclosure tested in this study. The reasons behind these findings might be first, agency theory represents an attractive platform for structuring corporate governance system but it seems to be Anglo-American centric, grounded in capitalistic theory and insensitive to non-economic forces that drive managerial choices in mixed economies. Secondly, corporate governance system derived from the agency theory might not be the best since it depends on the needs and culture of the companies as well as local prevailing laws and business environment. Thirdly, the agency theory concept, i.e. the agency conflicts between directors and shareholders does not seem to be fit in the Malaysian context since in Malaysia, the agency conflict seems to be between block shareholders and the minority shareholders. In addition, the accountants and financial analysts are interviewed to find out the reasons behind the findings and they opine that in order to improve the current Malaysian Code on Corporate Governance (2001), the government should implement a law which punishes non-compliance to corporate governance requirements and banks should be punished heavily if they do not comply. They further suggest that the current Code needs to be revised regularly to suit with the current business landscape and external auditors for the banks should be appointed by the Security Commission and Bank Negara Malaysia. In addition, by using simultaneous tests, the relationship among performance, risk and disclosure is examined based on the market discipline theory, signaling theory and risk and return theory. It is found that in the Malaysian context, the findings seem to be in line with theoretical expectation of market discipline and signaling theory, but not with risk and return theory. Therefore, the findings will be of interest to the stakeholders in general, and academicians, investors and regulators, in particular.